Potentiodynamic Study of the Effects of Nickel on The Electrodeposition of Zinc from Chloride Media - Zakiyya, Hanna; Kékesi, Tamás (International Journal of Engineering and Management Sciences, 2023)
Abstract. The potentiodynamic experiments of the nickel effects on the zinc electrodeposition have been done to understand the impact of Ni impurities on the electrowinning of Zn from spent pickling liquor. The nickel chloride solutions of Ni concentrations 90 and 1 g/dm3 were used as the electrolytes. The latter was also mixed with 90 g/dm3 Zn in the experiments. All the runs were carried out at room temperature with 40 mV/s continuous polarization speed and with 1/s sampling rate. It was observed that nickel electrodeposition from chloride media containing 90 g/dm3 Ni started with the generation of hydrogen bubbles, entirely blocking the cathode surface. Only a slight current development was observed until the polarization potential ~ -0,8 V. The visual observation showed bubbles also formed at the anode, which may represent chlorine and/or oxygen evolution. While, in the electrodeposition of nickel with only 1 g/dm3 Ni concentration in the electrolyte, metal deposition was hardly observed, but visible hydrogen bubbles constantly blocked the cathode surface. A similar tendency was observed in the mixed-solution electrolysis cell; the initial tiny bubbles accumulated at the cathode surface more than in the pure Zn solution. The enhancement of H2 evolution indicates how nickel deposition may contribute to the loss of useful current in the process of Zn electrodeposition. The mass of nickel deposited from the mixed solutions significantly decreases as the Ni concentration decreases in the electrolyte, while the mass of deposited zinc is relatively constant. It means that the purity of the produced Zn is appreciably higher – with respect to Ni – if nickel is efficiently eliminated from the solution before electrowinning.